Momentary Contentment - Ulrika Sandén; Lars Harrysson; Hans Thulesius (Grounded Theory Review: An International Journal)
This is a classic grounded theory based in longitudinal data from everyday life in an environment in Northern Norway characterized by long distances, a harsh climate and people living close to nature and each other. The place has a history of poverty and isolation. Yet, old survival strategies prevail despite modernisation. The theory reveals a culture of momentary contentment with three dimensions: Doing safety, destiny readiness and middle consciousness. This momentary contentment culture explains how the participants resolve their main concern of enjoying life. Doing safety means that common and individual acts create stability. Destiny readiness illuminates a discourse of acceptance, a way of thinking that, with the aid of linguistic strategies, prepares for life changing events. Middle consciousness shows a way of handling difficulties by dividing and separating different phenomena.